2023
DOI: 10.3390/agronomy13082024
|View full text |Cite
|
Sign up to set email alerts
|

Promotion Effect of Agricultural Production Trusteeship on High-Quality Production of Grain—Evidence from the Perspective of Farm Households

Xiaoyan Sun,
Youchao Wang,
Fengying Zhu
et al.

Abstract: Based on the survey data of five large grain-producing provinces in China, we have studied the promotion effect of the agricultural production trusteeship on the high-quality production of grain by using a propensity score matching method. The empirical results show that the high-quality production of the grain level increases by 0.292, with an increase of 87.4% after farm households participate in agricultural production trusteeship. The level of high efficiency, premiumization, greenization, and branding of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Based on the survey data of five major grain-producing provinces in China, Sun et al used the propensity score matching method to study the promotion effect of agricultural production trusteeship on grain quality production. The empirical results showed that after farmers' participation in the trusteeship of green agricultural production, the high-quality grain yield increased by 0.292 percentage points [43].…”
Section: Research On the Relationship Between Black Land Protection A...mentioning
confidence: 99%
“…Based on the survey data of five major grain-producing provinces in China, Sun et al used the propensity score matching method to study the promotion effect of agricultural production trusteeship on grain quality production. The empirical results showed that after farmers' participation in the trusteeship of green agricultural production, the high-quality grain yield increased by 0.292 percentage points [43].…”
Section: Research On the Relationship Between Black Land Protection A...mentioning
confidence: 99%
“…In the face of the reality of the low level of agricultural scale operation [1], high cost of grain production [2,3], and lack of a young and middle-aged labor force in rural areas [4][5][6], how to realize the transformation of agricultural operation modes and the improvement of grain production efficiency has become an important problem to be solved urgently [7][8][9]. The development of APTS and the promotion of service scale operation are the keys to answering this question [10]. As an important part of agricultural socialized service or agricultural productive service, APTS is an agricultural management mode in which farmers and other business entities independently entrust all or part of the farming, planting, prevention, and harvesting in agricultural production to service organizations or individuals to complete under the condition of retaining land management rights, mainly for the production link [11][12][13].…”
Section: Introductionmentioning
confidence: 99%